Analysis of Coal Consumption and Growth Nexus by Environmental Kuznets Curve - Bese, Emrah; Friday, Haven Swint (International Journal of Energy Economics and Policy, 2021)
In this study, New Zealand and Finland are examined by Autoregressive distributed lag (ARDL) model for the relationship between coal consumption and economic growth. For coal consumption and economic growth relationship, coal Kuznets curve is investigated for New Zealand for the period between 1980 and 2015 and is examined for Finland for the period between 1980 and 2013. Results of this study show that coal Kuznets curve is confirmed for New Zealand and Finland. Hao et al. (2016) confirmed coal Kuznets curve as this study confirmed in New Zealand and Finland. This study contributes to the current literature by verifying coal Kuznets curve for New Zealand and Finland. Coal Kuznets curve is also not investigated for these countries before. This study recommends further investigation of coal consumption-growth nexus carries importance since the only study in the literature for coal consumption-growth nexus belongs to this study for New Zealand and Finland. Keywords: Coal Kuznets Curve, Finland, New Zealand, ARDL Model JEL Classifications: Q4, Q5, O5 DOI: https://doi.org/10.32479/ijeep.10873